The Role of Christian Religious Education Teachers in Shaping Student Character Through Peace Education and Conflicts Resolution Among Students - Martha Anthoneta Talakua (Athena: Journal of Social, Culture and Society, 2023)
Peace education has emerged as one of the main factors for reducing conflicts among students, although its implementation in various Indonesian schools was limited. This qualitative study incorporated a literature review and aimed to investigate the role of Christian Religious Education (CRE) teachers in addressing conflicts among students by integrating peace education into CRE learning. Data were collected through observation and interviews. The results showed that the likelihood of both internal and external conflicts decreased when the teachers played a good role in educating students. Moreover, peace education constituted a long-term, effective effort against a culture of violence, specifically when implemented at an early age. CRE teachers were crucial in mitigating conflicts, making their promotion of peace education highly valuable in reducing such incidents. Furthermore, peace education is one of the solutions for shaping the character of students who embraced a peace-loving life